Abnormality of the Bile Tract (Luschka Duct): Case Report and Literature Review - Flores-García, Alba Elda; Ramírez-Vázquez, Jose Luis; Blaz-Zavala, Rogelio Agustin; Alonso de la Rosa, Jose Emmanuel; Diaz Mendez, Maria Fernanda; Flores-García, Luis Raymundo (British Journal of Healthcare and Medical Research, 2023)
Introduction: They are accessory bile ducts, less than 2 mm in diameter, they are in contact with the gallbladder bed, they depend on the right hepatic lobe most frequently. Clinical case: A 41-year-old male patient without comorbidities underwent laparoscopic cholecystectomy, during which bile leak from the accessory duct was detected. Double ligation was performed. During the postsurgical period, the patient presented a good clinical evolution. No evidence of collections, fistulas or any complications. Discussion: Different case series demonstrate that injuries during laparoscopic cholecystectomy are usually recognized during the procedure or more commonly in the immediate postoperative period. In the immediate postoperative period, the presence of bile output through a drain or peritoneal signs should imply a biliary injury. Localized accumulation of bile can produce a sterile bilioma , subhepatic or interhepatophrenic abscess . Conclusions: Surveillance must be exercised before any cholecystectomy, whether open or laparoscopic, since the presence of bile leak, its clinical presentation, diagnosis, classification, complexity and adequate treatment can reduce morbidity and mortality in the patient.